The Impact of Character.ai in Fostering Students Speaking Self-Confidence - Tiffany Azizzah, Devina; Muhamad Sofian Hadi (Tadris Pendidikan Bahasa Inggris IAIN Langsa, 2025)
This study investigates the impact of Character.ai (C.ai) on speaking self-confidence among Indonesian EFL learners in secondary school setting. Despite English’s global importance, EFL learners often struggle with speaking due to linguistic barriers (e.g., grammar, pronunciation) and psychological barriers (e.g., anxiety, low confidence). Leveraging AI’s potential, this quantitative study employs a pre-experimental one-shot case study design to evaluate Character.ai ‘s effectiveness. Data were collected from 37 eleventh-grade students at SMAN 01 Gunung Putri, Bogor, through post-tests assessing speaking skills (fluency, grammar, vocabulary, pronunciation, comprehension) and self-confidence (ability, assurance, engagement). The results revealed 41% students achieved of “Very Good” category, 43% students achieved of “Good” category, 11% students achieved of “Adequate” category. Statistical analysis (one-sample t -test, t (36) = 2.121, p = 0.041) confirmed a significant improvement in speaking confidence. However, challenges such as classroom noise and low-quality smartphone speakers affected the experience. While C.ai offers real-time feedback and personalized learning without teacher guidance, students’ confidence may also be influenced by other external factors. Thus, the findings highlight both the potential and limitations of using AI-based tools in language learning.